The Relationship Between the Level of Knowledge and Attitudes with Student Behavior in Choosing Healthy Snacks at SD N 05 Padang Pasir - Shofiyah Rahmadini; Gusni Rahma (Alifah Health Science Symposium Proceeding, 2023)
School-aged children are the biggest consumers of snack foods. Snacks are something that inseparable from life of elementary school children. A survey conducted by BPOM in 2018 reported that 42% of schools did not have regulations regarding PJAS (School Food Snacks), so children were at risk of eating unhealthy snacks. This study aims to look The Relationship Between Knowledge Level and Attitude with Students' Behavior in Choosing Healthy Snacks at SD N 05 Padang Pasir. The research method used quantitative with cross sectional study design. This research was conducted from March to August 2023. The sample for this research was all students in grades IV, V, and VI (Total Population) at SD N 05 Padang Pasir, totaling 64 students. Data was collected using questionnaire by means of interviews. Data analysis was performed univariately and bivariately using the chi-square test. The results showed that (48.4%) students had less knowledge in choosing healthy snacks, (51.6%) students had a negative attitude in choosing healthy snacks and (54.7%) students had poor behavior in choosing healthy snacks in SD N 05 Desert. Based on the results of statistical tests, there is a relationship between the level of knowledge (p-value = 0.005) and attitude (p-value = 0.025) with students' behavior in choosing healthy snacks at SD N 05 Padang Pasir. It was concluded that the level of knowledge and attitudes had a significant relationship with students' behavior in choosing healthy snacks. Students should pay more attention to the safety of the snacks that will be purchased and it is hoped that the school can provide education about healthy snacks to students and supervise the snacks that sold in the school environment.